Powered bipeds based on passive dynamic principles - Anderson, S.O.; Wisse, M.; Atkeson, C.G.; Hodgins, J.K.; Zeglin, G.J.; Moyer, B. (5th IEEE-RAS International Conference on Humanoid Robots, 2005, 2005)
We describe three bipedal robots that are designed and controlled based on principles learned from the gaits of passive dynamic walking robots. This paper explains the common control structure and design procedure used to determine the mechanical and control parameters of each robot. We present this work in the context of three robots: Denise, the Delft pneumatic biped, R1, a highly backdrivable electric biped, and R2, a hydraulic biped. This work illustrates the application of passive dynamic principles to powered systems with significant control authority